The Middle Wisconsinan History of the Laurentide Ice Sheet - Dredge, Lynda; Thorleifson, L. (Géographie physique et Quaternaire, 1987)
ABSTRACTEvidence for Middle Wisconsinan ice limits and climates comes from sites scattered around the periphery of the Laurentide Ice domain and from the Hudson Bay Lowlands. Interpretations are based on dated wood, peat, shell and sediment; biological climate indicators (chiefly cool-climate indicators); and stratigraphie sequences of both glacial and nonglacial units. The best evidence comes from the prairie provinces and the Great Lakes areas, both of which indicate substantial ice retreat from earlier southern glacial limits, and cool, boreal-tundra climates. The western arctic may have experienced an early warm period but both the western arctic — northwestern plains and eastern maritime areas may later have become ice accumulation areas. Three maps portray various possible ice limits. The first shows substantial ice cover in the arctic, but reduced ice cover in the prairies and Great Lakes, and expanded maritime ice caps (rather than Laurentide Ice) in the southeast and on Baffin Island. This ice mass distribution may reflect Middle Wisconsinan shifts in air masses and ocean currents. Ice volumes generated by this model are in accord with the marine oxygen isotope record and perceived global sea level changes. A modification to this model, which resolves some of the controversy in the Hudson Bay Lowlands, shows a calving bay penetrating into the heart of the ice sheet, induced by dynamic instability of the marine-based ice mass in Hudson Bay during relatively high glacial isostatic and eustatic seas. A third reconstruction portrays extensive climatically induced déglaciation and retains Laurentide ice only in parts of the northwest and Labrador-Ungava, with local ice in the Appalachian-Atlantic region. This model is based on alternative genetic interpretations of lithologic units and reassessment of age assignments.